The efficacy of mind-body (Baduanjin) exercise on self-reported sleep quality and quality of life in elderly subjects with sleep disturbances: a randomized controlled trial - Fan, Beifang; Song, Weidong; Zhang, Jihui; Er, Yuliang; Xie, Bo; Zhang, Huimin; Liao, Yuhua; Wang, Chengmin; Hu, Xiaohui; Mcintyre, Roger; Lee, Yena (Sleep & breathing, 2020)
Objectives To examine the efficacy of a 24-week Baduanjin exercise program on self-reported sleep quality and quality of life in community-dwelling elderly subjects with sleep disturbances. Methods Community-dwelling elderly men and women meeting criteria for sleep disturbances (i.e., Pittsburgh Sleep Quality of Index (PSQI) score ≥ 5) were recruited and randomized to a Baduanjin exercise intervention group or a control group. Participants in the intervention group completed five 45-min exercise sessions per week for 24 weeks, while those in control group were instructed to maintain their usual lifestyle behaviors. Results A total of 139 participants were enrolled and randomized. Sixty-two of 67 participants in the intervention group (response rate of 92.5%) and 57 of 72 participants (response rate of 79.6%) in the control group completed intervention and follow-up. The intervention group reported significant improvements in overall sleep quality after 24 weeks compared with those randomized to control (PSQI endpoint-to-baseline change = − 2.6 ± 4.0 vs. − 0.5 ± 4.2, time × group interaction p = 0.007). Intervention group participants had higher response rates at both week 12 (23.9% vs. 9.7%, p = 0.025) and week 24 (40.3% vs. 15.3%, p = 0.001) when compared with the control group. There was a trend that the intervention group had increased quality of life (The Short Form Health Survey [SF-36] endpoint=tobaseline change 6.3 ± 10.9 vs. 2.2 ± 10.9, time × group interaction p = 0.06) when compared with the control group. Conclusions Baduanjin exercise is an effective and feasible approach to improve self-reported sleep quality but less likely the quality of life in community-dwelling elderly men and women with sleep disturbances. Trial registration Effect of Baduanjin Exercise on the Elderly’s Sleep; http://www.chictr.org.cn/listbycreater.aspx ; ChiCTR1800014706, registered 1 January 2018.